Ramadan : The impact of fasting on hydration status towards elite football players on consecutive training session / Muhammad Rasydan Abdul Malek - Abdul Malek, Muhammad Rasydan (Faculty of Sport Science and Recreation, 2016)
The purpose of this study was to investigate the impact of Ramadan fasting on hydration status towards elite football players during consecutive training session. A total of twenty football players of UITM FC (N=20) were selected via purposive sampling participated in this study. The participants were age 22.5±1.395cm, weight 65.35±8.l3kg and height 1.69±O.2373 respectively . In four days of training session during Ramadan, hydration status measures were made before and after training session. The urine specific gravity, urine pH level, urine color and urine volume are the parameters were used to measures hydration status. Result showed that there was a significant difference (p<O.05) in urine specific gravity, urine color and urine volume before and after training session. In the urine pH level, result showed that there was no significant difference (p>O.05) before and after training session. As for the conclusion, the findings in this study indicated that urine specific gravity, urine color and urine volume showed significant results among Malaysia elite football players during Ramadan fasting. However, after four days of training session, there was no significant changed of urine pH level as the player were in hypohydrated state after training session.